ANALYSIS OF WI-FI NETWORK QUALITY IN TANJUNGPURA UNIVERSITY LIBRARY BUILDING - Nauvaldi, Syafrizal; Pontia, F. Trias; Tjahjamooniarsih, Neilcy (Faculty of Engineering, Universitas Tanjungpura, 2023)
Tanjungpura University Library Building as a place that is often crowded with students who use Wi-Fi networks, requires good Wi-Fi signal quality to support smooth and efficient internet access to various digital resources.Wi-Fi data retrieval is inside the Tanjungpura University Library Building, Measuring RSSI (Received Signal Strength Indicator) parameters in the Tanjungpura University Library Building area using the application G-NetWi-Fi, where measurements are carried out by the walk test method using the G-NetWi-Fi application, Make data analysis and conclusions from the results of measuring RSSI (Received Signal Strength Indicator) parameters at the Tanjungpura University Library Building.Analysis of the results to be carried out is to analyze measurement data to compare measurement results with RSSI (Received Signal Strength Indicator) quality standards. Based on the measurements made, there are many measurement data that show the quality of RSSI ranging from good, normal and bad, from the Wi-Fi of Tanjungpura University Library on each route. For the RSSI value obtained by each route, the point and time will certainly vary. Measurement results This depends on the route passed by the user from the Tanjungpura University Library Wi-Fi. Because the more users, the greater the RSSI value that will be obtained.